Combined proton NMR wideline and NMR relaxometry to study SOM-water interactions of cation-treated soils - Schaumann Gabriele E.; Diehl Dörte; Bertmer Marko; Jaeger Alexander; Conte Pellegrino; Alonzo Giuseppe; Bachmann Jörg (Journal of Hydrology and Hydromechanics, 2013)
Focusing on the idea that multivalent cations affect SOM matrix and surface, we treated peat and soil samples by solutions of NaCl, CaCl2 or AlCl3. Water binding was characterized with low field 1H-NMR-relaxometry (20 MHz) and 1H wideline NMR spectroscopy (400 MHz) and compared to contact angles.